2011
DOI: 10.1021/ef200605a
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Microscopic Displacement Mechanisms of Alkaline Flooding for Enhanced Heavy-Oil Recovery

Abstract: In this study, the microscopic displacement mechanisms of alkaline flooding for enhanced heavy-oil recovery are investigated using a micromodel. It has been observed that alkaline flooding exhibits a better sweep efficiency than waterflooding, and the serious viscous fingering is significantly reduced. The main microscopic mechanisms of alkaline flooding for enhanced heavy-oil recovery are that the alkaline solution penetrates in crude oil and water drops are, subsequently, formed inside the oil phase, which c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(50 citation statements)
references
References 13 publications
0
50
0
Order By: Relevance
“…This phenomenon is particularly relevant for heavy oil recovery as observed in the works of Pei et al (2011), and later, by Dong et al (2012). A bank of viscous (W/O) emulsion forms when an acidic heavy oil is displaced by an alkaline solution prepared in a high-salinity brine in a porous medium.…”
Section: Alkali-surfactant Floodingmentioning
confidence: 91%
“…This phenomenon is particularly relevant for heavy oil recovery as observed in the works of Pei et al (2011), and later, by Dong et al (2012). A bank of viscous (W/O) emulsion forms when an acidic heavy oil is displaced by an alkaline solution prepared in a high-salinity brine in a porous medium.…”
Section: Alkali-surfactant Floodingmentioning
confidence: 91%
“…In other words, the formation of emulsion is conductive to the recovery of residual oil [16]. Pei et al [17,18] and Dong et al [18] studied the alkali flooding mechanism through microscopic model, which implied that alkali permeated into the oil phase to form emulsion was important for EOR.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that the emulsions, either generated in situ or injected externally have the tendency to block the swept out pores and divert the flow to the bypassed region [3][4][5]. On the other hand, in some other situations emulsions help to entrain the oil into the flowing aqueous phase [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…However, the surfactant-stabilized emulsion do not have a good 3 stability under harsh reservoir conditions, and the mobility of a surfactant-stabilized emulsion is generally much larger, thus the mobility control of these emulsions have a certain degree of limitations. Nanoparticle can also be used to stabilize emulsions and have several advantages compared to surfactant-stabilized emulsions.…”
Section: Introductionmentioning
confidence: 99%